Radiolytic degradation of BDE-209 in rice-vegetable rotation soils induced by electron beam irradiation. (1st October 2021) - Zhao, Pengfei; Ye, Qingfu; Zheng, Yaoying; Whalen, Joann K.; Zhang, Sufen; Wang, Wei
Abstract: Deca-brominated diphenyl ether (BDE-209) is shown to be persistent in soil and it's urgent to find an effective method to remove BDE-209 from contaminated soil. In this study, the investigation of BDE-209 degradation in three different rice-vegetable rotation soils induced by electron beam (E-beam) irradiation under flooded and non-flooded conditions was conducted. The reductive efficiency of 14 C-BDE209 reached the highest level at 50 kGy and the values in flooded soils of rice-eggplant rotation soil (RES), rice-peanut soil (RPS), and rice-chili pepper soil (RCS) were 93.5%, 87.2%, and 73.8%, respectively. The reductive efficiencies in non-flooded soils of RES, RPS, and RCS were 73.4%, 81.0%, and 78%, respectively. The D0.5 values (dose required for reducing 50% BDE-209) of BDE-209 in non-flooded soils were lower than those in flooded soils, suggesting greater degradation efficiency of BDE-209 in non-flooded soils than in flooded soils. The BDE-209 was degraded into higher-brominated PBDEs and lower-brominated PBDEs by E-beam irradiation. The results demonstrate that BDE-209 in the soil can be degraded by E-beam irradiation, non-flooded condition is better than flooded condition for the removal of BDE-209, and the main degradation mechanism of BDE-209 by E-beam irradiation is debromination. This study provides a rapid and effective method for degrading BDE-209 that is persistent in soils, and has important implications for the remediation of soil contaminated by PBDEs in and around E-waste dismantling areas. Graphical abstract: Image 1 Highlights: Electron beam irradiation can effectively remove BDE-209 in contaminated soil. E-beam-radiolytic decomposition rate of BDE-209 increases with radiation dose. Irradiation cannot promote the mineralization of BDE-209 in contaminated soil. The remediation method is fast, effective, and environmentally friendly.